Anti Hyperlipidemic and Anti-Oxidant Activities of Spirulina Platensis Microalgae in Heat-Stressed Rats - Khashayar Bahramsari, Melika Tavakoli, Akram Pasandideh Tashakori, Hamed Nikpourian, Yasaman Allahgholi, Farhad Jazideh (International Journal of Modern Agriculture, 2021)
Objective: The current research was performed to investigate the effect of oral supplementing of Spirulina platensis microalgae (SPM) on some blood biochemical parameters, antioxidant status and growth performance of Wistar rats kept under heat stress (HS) condition (32Â°C for 6 h). Methods: Forty Wistar male rats were randomly grouped into five groups. The animals in control group received distilled water and other groups received 5, 10, 15 and 20 mg of SPM/kg of body weight (BW), for 35 days. BW was recorded at the beginning and at the end study to determine the changes in the BW and feed intake (FI) rats was daily measured. The blood samples were collected for measurement of glucose, cholesterol, triglycerides, high-density lipoprotein-cholesterol (HDL-C), malondialdehyde (MDA) or activities of superoxide dismutase (SOD) and glutathione peroxidase (GPX). Results: Our results showed that the serum concentrations of cholesterol, triglycerides and MDA were significantly lower in rats supplemented with 15 and 20 mg of SPM/kg of BW compared to other animals (P<0.05). Activities of GPX and SOD were elevated in animals treated with SPM at 20 mg of SPM/kg of BW when compared with other rats (P<0.05). The serum concentration of HDL-C, glucose, BW and FI were not influenced in treated animals (P>0.05). Conclusion: It can be concluded that oral supplementing the SPM at high levels, especially 20 mg of SPM/kg of BW, was optimum way to alleviate the negative effect of HS on blood parameters or antioxidant status in rats maintained under HS condition.